The Impact of English Week Program on Students’ Interactive Speaking Performance at an Islamic Boarding School: An EFL Teacher’s Perspective - Siti Zahra Fauziah; Iskhak Said; Andi Rustandi (Universitas Galuh, 2026)
Speaking is one of the most crucial skills in English language learning; and interactive speaking is challenging for students, especially those in boarding schools with limited exposure. Although previous studies have examined students' perceptions, there has been little research conducted on teachers' perspectives. This study aims to explore an EFL teacher's perspective on the implementation and impact of the English Week program on students' interactive speaking performance and to identify the challenges they faced during the program. The researcher employed a qualitative case study approach, utilizing a snowball sampling technique, followed by non-participant observation and semi-structured interviews with an EFL teacher at an Islamic boarding school in Tasikmalaya. The results showed that the program successfully stimulated students' interactive speaking skills by combining formal and informal activities. The teacher employed scaffolding strategies and served as a facilitator and motivator. As a result of this research, students demonstrated increased confidence and improved interaction skills. However, there were other challenges, including a limited vocabulary, fluctuating motivation, and inadequate facilities. Based on this research, the English Week program has a positive impact on students' interactive speaking skills through creative and varied learning strategies, structured management, and a supportive learning environment. Understanding the teacher's perspective confirms the importance of institutional support and continuous program development. Future research is suggested to dig out the students’ perceptions on this related topic with a large sample to obtain a broad insight.